An algebra problem by Dev Sharma

Algebra Level 5

If x x and y y are real numbers and ( 2 x 2 6 x + 6 ) ( y 2 2 y + 7 ) = 9 (2x^2 - 6x + 6)(y^2 -2y + 7) = 9 then find the value of x + y x+ y .


The answer is 2.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Surya Prakash
Oct 22, 2015

Before giving away my solution I wanna give you some information which is used in this problem.

The function f ( x ) = a x 2 + b x + c f(x) = ax^2 + bx+c has minimum which is equal to 4 a c b 2 4 a \dfrac{4ac-b^2}{4a} and it occurs at b 2 a \dfrac{-b}{2a} if a > 0 a>0 and vice versa.


So, 2 x 2 6 x + 6 2x^2 -6x +6 and y 2 2 y + 7 y^2 -2y+7 has minimum values as the coefficient of x 2 x^2 in both cases is > 0 >0 . So,

2 x 2 6 x + 6 4 × 2 × 6 36 4 × 2 = 3 2 2x^2 - 6x + 6 \geq \dfrac{4\times 2 \times 6 - 36}{4 \times 2} = \dfrac{3}{2} and equality holds at x = 3 2 x= \dfrac{3}{2} .

Similarly, y 2 2 y + 7 6 y^2 - 2y + 7 \geq 6 and equality holds at y = 1 y= 1 .

Then, ( 2 x 2 6 x + 6 ) × ( y 2 2 y + 7 ) 9 \left(2x^2 - 6x + 6 \right) \times \left( y^2 - 2y + 7 \right) \geq 9 and equality hold when x = 1.5 x= 1.5 and y = 1 y=1 . But, ( 2 x 2 6 x + 6 ) × ( y 2 2 y + 7 ) = 9 \left(2x^2 - 6x + 6 \right) \times \left( y^2 - 2y + 7 \right) = 9 . So, x = 1.5 x= 1.5 and y = 1 y=1 .

Therefore, x + y = 2.5 x+y = \boxed{2.5} .

Moderator note:

Good observation about the minimum values. One additional condition to be aware of, is that both of these minimums are positive, in order to ensure that we have a unique solution.

Great observation......Thank u for that technique....

Anubhav Mahapatra - 3 years, 10 months ago

We can rewrite the given equation as

2 ( x 2 3 x + 3 ) ( y 2 2 y + 7 ) = 2 ( ( x 3 2 ) 2 + 3 4 ) ( ( y 1 ) 2 + 6 ) = 9 2(x^{2} - 3x + 3)(y^{2} - 2y + 7) = 2((x - \frac{3}{2})^{2} + \frac{3}{4})((y - 1)^{2} + 6) = 9

2 ( x 3 2 ) 2 ( y 1 ) 2 + 12 ( x 3 2 ) 2 + 3 2 ( y 1 ) 2 = 0. \Longrightarrow 2(x - \frac{3}{2})^{2}(y - 1)^{2} + 12(x - \frac{3}{2})^{2} + \frac{3}{2}(y - 1)^{2} = 0.

Since both ( x 3 2 ) 2 , ( y 1 ) 2 (x - \frac{3}{2})^{2}, (y - 1)^{2} are 0 \ge 0 we require that both equal 0. 0. This implies that x + y = 3 2 + 1 = 2.5 . x + y = \frac{3}{2} + 1 = \boxed{2.5}.

Yugesh Kothari
Nov 5, 2015

Let f ( x ) = 2 x 2 6 x + 6 a n d f ( y ) = y 2 2 y + 7 f\left( x \right) ={ 2x }^{ 2 }-6x+6\quad and\quad f\left( y \right) ={ y }^{ 2 }-2y+7

Given, f ( x ) f ( y ) = 9 f\left( x \right) f\left( y \right) = 9

So, f ( y ) = 9 f ( x ) f\left( y \right) =\frac { 9 }{ f\left( x \right) }

Now, For y y to be real, 0 \triangle \ge 0 Which means, f ( x ) 3 2 f\left( x \right) \le \frac { 3 }{ 2 }

=> f ( x ) 3 2 0 f\left( x \right) -\frac { 3 }{ 2 } \le 0

=> 2 ( x 3 2 ) 2 0 2{ \left( x-\frac { 3 }{ 2 } \right) }^{ 2 }\le 0\quad and so x = 3 2 x=\frac { 3 }{ 2 }

Now, f ( 3 2 ) = 3 2 = > f ( y ) = 9 f ( x ) = 6 f\left( \frac { 3 }{ 2 } \right) =\frac { 3 }{ 2 } \quad =>\quad f\left( y \right) =\frac { 9 }{ f\left( x \right) } =6

Which gives y = 1 y=1 and hence x + y = 2.5 x+y=2.5

Aareyan Manzoor
Oct 31, 2015

let { 2 x 2 6 x + 6 = a 2 x 2 6 x + 6 a = 0 y 2 2 y + 7 = 9 a y 2 2 y + 7 9 a = 0 \begin{cases} 2x^2-6x+6=a\Longrightarrow 2x^2-6x+6-a=0\\ y^2-2y+7=\dfrac{9}{a}\longrightarrow y^2-2y+7-\dfrac{9}{a}=0\end{cases} note that x,y must be real hence both equation must have a discriminant \geq 0. we get that: { 6 2 4 2 ( 6 a ) 0 a 1.5 2 2 4 ( 7 9 a ) 0 a 1.5 \begin{cases} 6^2-4*2(6-a)\geq 0\Longrightarrow a\geq 1.5\\ 2^2-4(7-\dfrac{9}{a})\geq 0\Longrightarrow a\leq 1.5\end{cases} we see that a must be 1.5, putting this in individual equations, { 2 x 2 6 x + 6 = 1.5 x = 1.5 y 2 2 y + 7 = 9 1.5 y = 1 \begin{cases}2x^2-6x+6=1.5\Longrightarrow x= 1.5\\ y^2-2y+7=\dfrac{9}{1.5}\longrightarrow y = 1\end{cases} x + y = 1.5 + 1 = 2.5 x+y=1.5+1=\boxed{2.5}

Edwin Gray
Jun 23, 2018

We write the 2 equations: (1) 2x^2 - 6x + 6 = t, and (2) y^2 -2y + 7 = 9/t. Solve each one by the quadratic formula, and get: (3) 4x = 6 +/- sqrt(36 - 8(6 - t), and (4) 2y = 2 +/- sqrt $ - 4(7 - 9/t). Since we are wanting a single solution fot x + y, both discriminants must vanish, which happens when t = 1.5. Then x = 1.5, y = 1, and x + y = 2.5.Ed Gray

Tom Engelsman
Oct 31, 2015

If one solves for x in terms of y, then:

2(x^2 - 3x + 3) = 9/(y^2 - 2y +7);

or x^2 - 3x = 9/[2*(y^2 - 2y +7)] - 3;

or x^2 - 3x + 9/4 = 9/[2*(y^2 - 2y +7)] - 3 + 9/4;

or (x - 3/2)^2 = 9/[2*(y^2 - 2y +7)] - 3/4;

or x - 3/2 = (+/-)sqrt{9/[2*(y^2 - 2y +7)] - 3/4};

or x = 3/2 (+/-) (y-1)/2 * sqrt[-3/(y^2 - 2y + 7)].

The quadratic equation y^2 - 2y + 7 is strictly positive for all real y since (-2)^2 - 4(1)(7) < 0 (by the discriminant test). Hence x can only be real iff y = 1, which yields x = 3/2 and x + y = 5/2 (or 2.5).

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...